Emerging therapy for adrenocortical carcinoma. (November 2014) - Aufforth, Rachel D; Nilubol, Naris
Adrenocortical carcinoma (ACC) is a very rare and aggressive tumor with dismal outcomes. Best current treatments include complete surgical resection for localized resectable disease and systemic therapy with mitotane alone or in combination for advanced ACC. Advances in molecular genetic profiling of ACC have created multiple new targets for potential treatment options in ACC. This article reviews the current treatment options available for ACC and discusses the potential new targets identified through molecular profiling.